Synthesis of ï§-Al2O3 Catalyst Support from Kaolin of Indonesian Origin - Tjokorde Walmiki Samadhi; Subagjo Subagjo; Kevin R. Lismana; Khasin Fuadi (Journal of Engineering and Technological Sciences, 2011)
Kaolin  has  been  identified  as  a  potential  raw  material  for  the production of  ï§-Al2O3  for  hydrotreating  catalyst support. This work explores the technical  feasibility  of  applying  the  potassium  hydroxide  (KOH)  e xtraction synthesis route on kaolin  from the Belitung  Island  in Indonesia. The application of  a  published  synthesis  method  to  Belitung  kaolin  requires  an  approximately twofold  increase  in  kaolin  calcination  time,  an  increase  in  kaolin  calcination temperature from 950 to 1000 °C, and a tenfold increase in metakaolin extraction time, to obtain a specific surface area higher than 200 m2/g. The highest specific surface area of 233 m2/g was obtained when  the kaolin was calcined at 1000 °C for 24 hours, and the  metakaolin  was extracted by concentrated KOH  solution for 12 hours.  Phase characterization of the final product confirmed the formation of ï§-Al2O3, but with the inclusion of low-surface area ï¡-Al2O3 phase.